2021
DOI: 10.2478/sgem-2021-0026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the pile skin resistance formation

Abstract: This paper introduces a method based on a static load test which is aimed to verify the mechanism of the piles soil–skin interaction. The authors base their analysis on detailed data from static load test with extensometers on CFA piles. The main goal of the research is to determine the proper method of examining how the skin of the pile and soil interacts and apply it to practical engineering practice. As the first stage of the research is limited to the available set of piles, the authors make assumptions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Instead, it considered the mechanism of the bending of the soil space around the pile according to Kirchhoff's principle, which allowed to consider the entire soil body. An analysis of the experimental results showed that the applied mathematical description validates the presented approach [28]. The verification of the static load test results showed a positive correlation between the calculation and the field investigation results [22].…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Instead, it considered the mechanism of the bending of the soil space around the pile according to Kirchhoff's principle, which allowed to consider the entire soil body. An analysis of the experimental results showed that the applied mathematical description validates the presented approach [28]. The verification of the static load test results showed a positive correlation between the calculation and the field investigation results [22].…”
Section: Introductionmentioning
confidence: 52%
“…An analysis of the experimental results showed that the applied mathematical description validates the presented approach [28]. The verification of the static load test results showed a positive correlation between the calculation and the field investigation results [22]. Multiple studies have been conducted on specific soil geotechnical parameters based on static load testing [9; 14; 15; 25; 33].…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations